2020
DOI: 10.1002/jmor.21121
|View full text |Cite
|
Sign up to set email alerts
|

Skull morphology of bottlenose dolphins from different ocean populations with emphasis on South America

Abstract: The bottlenose dolphin, genus Tursiops, is cosmopolitan occurring in tropical and temperate regions, with morphological variation between and within different oceans.Since the genus' taxonomy has been under discussion for a long time, this work aimed at analyzing the cranial variability of T. truncatus from different regions of the world.Geometric Morphometrics analyses were performed in 201 skulls of adult specimens, on dorsal, ventral, and lateral views, from the Eastern North Pacific, Eastern North Atlantic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…They are regularly sighted along a narrow stretch of the coast in strong association with estuaries and river mouths (see Laporta et al, 2016 for a review). These costal dolphins were recently recognized as a different species (Lahille's bottlenose dolphin, Tursiops gephyreus- Wickert et al, 2016;Hohl et al, 2020) of the abundant, worldwide-distributed common bottlenose dolphin (T. truncatus), although Marine Mammalogy's Committee on Taxonomy argues that the lineages should be recognized at subspecies level 2018 (Costa et al, 2016(Costa et al, , 2019Marine Mammalogy's Committee on Taxonomy, 2018). Due to the low number of individuals representing the entire lineage, and evidence of decline at least in part of its range due to bycatch and other unknown factors, the Lahille's bottlenose dolphin was recently listed as Vulnerable under criterion D1of the IUCN (Vermeulen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…They are regularly sighted along a narrow stretch of the coast in strong association with estuaries and river mouths (see Laporta et al, 2016 for a review). These costal dolphins were recently recognized as a different species (Lahille's bottlenose dolphin, Tursiops gephyreus- Wickert et al, 2016;Hohl et al, 2020) of the abundant, worldwide-distributed common bottlenose dolphin (T. truncatus), although Marine Mammalogy's Committee on Taxonomy argues that the lineages should be recognized at subspecies level 2018 (Costa et al, 2016(Costa et al, , 2019Marine Mammalogy's Committee on Taxonomy, 2018). Due to the low number of individuals representing the entire lineage, and evidence of decline at least in part of its range due to bycatch and other unknown factors, the Lahille's bottlenose dolphin was recently listed as Vulnerable under criterion D1of the IUCN (Vermeulen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…They found that the ventral region allowed for the detection of two morphological groups, but the discrimination observed in the dorsal region was higher, suggesting that adaptive processes occur with lower intensity in the ventral region than in the dorsal region and, consequently, result in a less variable region. The significant differences found by Ngqulana et al (2019) and by Hohl et al (2020) in the ventral view were probably due to the use of landmarks related to pterygoids that detected an area with higher plasticity associated with the breathing apparatus. In that sense, different methodologies can produce different results.…”
Section: Discussionmentioning
confidence: 85%
“…Fifteen landmarks were used to obtain the geometric configuration of the dorsal view, 13 for the ventral view, and 15 for the lateral view (Table 1, Figure 2). The selection of landmarks was based for dorsal and ventral views on a previous analysis for Amaral et al, (2009) and lateral view on Hohl et al, (2020) and the cranial bones nomenclature description for common bottlenose dolphins was based to Hohl et al, (2020) supported in the proposed Mead and Fordyce (2009). The coordinates (X, Y) of each landmark were transformed to new coordinates using the generalized Procrustes superposition method (Dryden & Mardia, 1998) to remove shape variation associated with the size, position, F I G U R E 1 Stranding areas of the 17 skulls from Tursiops truncatus.…”
Section: Image Acquisition and Definition Of Landmarksmentioning
confidence: 99%
“…The name has been used periodically at the species level by South American researchers, and there have been several recent suggestions that the form is either a valid species or subspecies. Wickert et al (2016) and Hohl et al (2020) suggested that there are indeed species-level differences and that the name should be resurrected. However, this has not been accepted by the Committee on Taxonomy (SMM, 2020), and the name is currently considered to be a junior synonym of Tursiops truncatus and the senior synonym of the subspecies Tursiops truncatus gephyreus (the coastal form of bottlenose dolphin from the western South Atlantic -see Costa et al, 2016Costa et al, , 2021Wang et al, 2021).…”
Section: Tursiops Gephyreus Lahille 1909mentioning
confidence: 99%